West Africa regional training on ENACTS-related capacity for National Meteorological Services and the Regional Climate Centre - Minoungou, Bernard; Houngnibo, Mandela C.; Nsengiyumva, Gloriose; Lona, Issaka; Namodji, Lucie; Halidou, Tinni Seydou; Hamatan, Mohamed; Dinku, Tufa; Ali, Abdou; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The AICCRA West Africa cluster in collaboration with AGRHYMET and IRI organized a regional capacity training on ENACTS tools. The Agence Nationale de la Météorologie (ANAM) of Burkina Faso hosted National Meteorological Services as well as the Regional Climate Center (AGRHYMET) experts from two AICCRA and three non-AICCRA countries from West Africa to build their capacity to produce more tailored and real-time climate information and services for decision making. Capacity building focused on the following topics: • Use of Climate Data Tool (CDT) for data organization, quality control, merging of different datasets, data analysis, and visualization; • Introduction to IRI’s Automatic Weather Station Data Tool (ADT); and • Use of IRI’s Next Generation (NextGen) seasonal forecast system for seasonal rainfall forecast.